ANALISIS STRATEGI KOMUNIKASI PEMASARAN SKINTIFIC DI TIKTOK SHOP MELALUI AKUN MEDIA SOSIAL SKINTIFIC_ID - Karin Feliana; Muhammad Fikri Gissani (JURNAL SIGNAL, 2026)
The development of digital technology has transformed the marketing landscape, leading to a Digital technology development has shifted marketing from conventional to digital media. TikTok, with interactive features and dynamic visual content, is widely used by companies to build consumer relationships and enhance brand awareness. This study analyzes Skintific’s marketing communication strategies on TikTok Shop via the @skintific_id account, focusing on audience engagement, brand image strengthening, and purchase decisions. Using a descriptive qualitative method and secondary data from industry reports, literature, and Skintific’s TikTok content, the study finds that Skintific effectively applies Marketing 4.0 through informative short videos, collaborations with beauty influencers, and interactive live shopping. These strategies increase engagement, reinforce brand image, and influence purchase decisions. The study concludes that TikTok Shop is a responsive and personal marketing channel, recommending other brands leverage it through creative content, direct interaction, and tailored messages to reach young digital audiences and stay competitive.